Pemeriksaan Kadar Bakteriologis Pada Susu Merk X Penyebab Foodborne Disease Sebelum dan Sesudah Kedaluwarsa - Rizki Rahayu Putri; Nopi Sani q; Yesi i Nurmalasar; Efrida Warganegara (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Milk as a food source for calves and humans contains very high nutrients but was easily contaminated by microorganisms. And if it consumed, bacteria-contaminated milk can cause foodborne disease. Purpose: This study was conducted to determine bacteriological levels in UHT milk brand X causing foodborne disease before and after expiration. Research Method: The research method used in this study is an experimental or experimental research. The data obtained were stated in a descriptive qualitative manner. The result: Bacteriological levels of UHT milk brand X a month before and after expiration had the closest estimated value <3 APM / ml. Conclusion: From the research that has been done, it is obtained that the X brand UHT milk a month before and after the expiration date has the closest estimated value <3 APM / ml based on SNI 2897: 2008 which explains that the two X brand UHT milk is not contaminated by coliform bacteria.